2015
DOI: 10.1007/s40272-014-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiepileptic Drugs on Bone Health and Growth Potential in Children with Epilepsy

Abstract: Measures to correct vitamin D deficiency, calcium intake should be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 70 publications
1
18
0
1
Order By: Relevance
“…Our study reemphasizes that long‐term AED polytherapy intake (>1 AED) is an important risk factor for children with epilepsy to develop vitamin D deficiency. Our findings are similar with those of other studies showing the negative impact of AED polytherapy and support the results of other studies showing that AED polytherapy exerted a negative impact on bone mineral density . This highlights the importance for clinicians to avoid treating children with AED polytherapy whenever possible due to adverse effects to bone health.…”
Section: Discussionsupporting
confidence: 91%
“…Our study reemphasizes that long‐term AED polytherapy intake (>1 AED) is an important risk factor for children with epilepsy to develop vitamin D deficiency. Our findings are similar with those of other studies showing the negative impact of AED polytherapy and support the results of other studies showing that AED polytherapy exerted a negative impact on bone mineral density . This highlights the importance for clinicians to avoid treating children with AED polytherapy whenever possible due to adverse effects to bone health.…”
Section: Discussionsupporting
confidence: 91%
“…Further studies will be needed to understand these epigenetic changes in biological and clinical perspectives. Nonetheless, it is noteworthy that many clinical studies have suggested that chronic epilepsy or perhaps the long-term use of antiepileptic drugs may cause growth/developmental problems in children, while abnormal steroid hormone metabolism and certain forms of osteopathy are noted in patients under drug treatments7475767778. In the current cohort of male and female patients and controls, the mean ages were 25 to 35 years, while one-third of the patients with epilepsy onset before 12 year-old (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent review of 32 cross-sectional, cohort, case-control, and randomised controlled trials suggested that reduced bone density, impaired bone growth, and vitamin D deficiency may be seen in children treated with anticonvulsants. 25 In our study, individual vitamin D daily intake was calculated by dietitians. Sun exposure was limited in the institutional setting.…”
Section: Discussionmentioning
confidence: 99%